Expert Overviews Provide Updates in Parkinson's Disease and Movement Disorders - Cunningham, Muriel (MD Conference Express, 2014)
This article presents a summary of essential tremor and treatment options, an overview of Parkinson's disease, as well as discusses the latest genetic classification and treatment information for patients with dystonia.